Forms of Care: Chimamanda Ngozi Adichie’s Americanah (2014), Agency, and Decolonial Feminism - McCann, Fiona (Études littéraires africaines, 2021)
Cet article explore la politique féministe telle qu’elle est représentée dans le roman Americanah de Chimamanda Ngozi Adichie, ainsi que la manière dont ce féminisme s’entremêle avec des formes de care. Je cerne les contours de l’engagement affiché de l’autrice pour le féminisme intersectionnel, tout en pointant quelques angles morts. Après avoir situé l’oeuvre d’Adichie dans le contexte des féminismes postcolonial, populaire et décolonial, j’étudie l’importance des cheveux et la question plus générale de l’agentivité. Dans la dernière partie, je démontre que la poétique du care développée dans le roman n’adhère pas totalement au féminisme décolonial en raison de l’invisibilité relative des structures néo-coloniales à l’oeuvre au Nigeria pendant la période contemporaine.
Keywords: afro-féminisme; agentivité; approches et analyses; arts; care; discipline; féminisme décolonial; féminismes noirs; littérature; militance; politique; ressource en ligne; thématiques; études littéraires

Indigenous women and feminism: politics, activism, culture - Suzack, Cheryl; Huhndorf, Shari M.; Perreault, Jeanne; Barman, Jean (UBC Press, 2010)
"Can the specific concerns of Indigenous women be addressed within current mainstream feminist and post-colonial discussions? Indigenous Women and Feminism: Politics, Activism, Culture proposes that a dynamic new line of inquiry – Indigenous feminism – is necessary to truly engage with the crucial issues of cultural identity, nationalism, and decolonization particular to Indigenous contexts. Through the lenses of politics, activism, and culture, this wide-ranging collection examines the historical roles of Indigenous women, their intellectual and activist work, and the relevance of contemporary literature, art, and performance for an emerging Indigenous feminist project. The questions at the heart of these essays – What is at stake in conceptualizing Indigenous feminism? How does feminism relate to Indigenous claims to land and sovereignty? What lessons can we learn from the past? How do Indigenous women engage ongoing violence and social and political marginalization? – cross disciplinary, national, academic, and activist boundaries to explore in depth the unique political and social positions of Indigenous women."–Page 4 de la couverture."A vital and sophisticated discussion that will change the way we think about modern feminism, Indigenous Women and Feminism will be invaluable to scholars, activists, artists, community organizers, and those concerned with Indigenous and feminist issues at home and abroad."– Résumé de l'éditeur.
Le texte de Tsosie, Rebecca (2011). Native Women and Leadership: An Ethics of Culture and Relationship a été donné en lecture au cours POL4105.
Keywords: activisme; approches et analyses; arts; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; militance; pol4105; premier cycle; premières nations; système colonial; systèmes d'oppressions; territoire; thématiques; études autochtones; études féministes; études littéraires

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Minnesota University Press, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Contenu: Introduction / Aamir Mufti and Ella Shohat – pt. I. Contesting Nations. 1. Zionism from the Standpoint of Its Victims / Edward W. Said. 2. Sephardim in Israel: Zionism from the Standpoint of Its Jewish Victims / Ella Shohat. 3. Of Balkans and Bantustans: Ethnic Cleansing and the Crisis in National Legitimation / Rob Nixon. 4. "No Longer in a Future Heaven": Gender, Race, and Nationalism / Anne McClintock. 5. Currying Favor: The Politics of British Educational and Cultural Policy in India, 1813-54 / Gauri Viswanathan. 6. The Nation as Imagined Community / Jean Franco – pt. II. Multiculturalism and Diasporic Identities. 7. On the Question of a Theory of (Third) World Literature / Madhava Prasad. 8. Caliban Speaks Five Hundred Years Later / Roberto Fernandez Retamar. 9. The Local and the Global: Globalization and Ethnicity / Stuart Hall. 10. Multiculturalism and the Neoconservatives / Robert Stam. 11. Shuckin' Off the African-American Native Other: What's "Po-Mo" Got to Do with It? / Wahneema Lubiano. 12. Identity, Meaning, and the African-American / Michael Hanchard. 13. Just Looking for Trouble: Robert Mapplethorpe and Fantasies of Race / Kobena Mercer – pt. III. Gender and the Politics of Race. 14. Under Western Eyes: Feminist Scholarship and Colonial Discourses / Chandra Talpade Mohanty. 15. Traddutora, Traditora: A Paradigmatic Figure of Chicana Feminism / Norma Alarcon. 16. American Indian Women: At the Center of Indigenous Resistance in Contemporary North America / M. Annette Jaimes and Theresa Halsey. 17. "On the Threshold of Woman's Era": Lynching, Empire, and Sexuality in Black Feminist Theory / Hazel V. Carby. 18. Making Empire Respectable: The Politics of Race and Sexual Morality in Twentieth-Century Colonial Cultures / Ann Laura Stoler. 19. Age, Race, Class, and Sex: Women Redefining Difference / Audre Lorde. 20. Gender Is Burning: Questions of Appropriation and Subversion / Judith Butler. 21. Sisterhood: Political Solidarity between Women / Bell Hooks – pt. IV. Postcolonial Theory. 22. Not You/Like You: Postcolonial Women and the Interlocking Questions of Identity and Difference / Trinh T. Minh-ha. 23. Is the "Post-" in "Postcolonial" the "Post-" in "Postmodern"? / Kwame Anthony Appiah. 24. The World and the Home / Homi K. Bhabha. 25. Reading Africa through Foucault: V.Y. Mudimbe's Reaffirmation of the Subject / Manthia Diawara. 26. Teaching for the Times / Gayatri Chakravorty Spivak. 27. Postcolonial Criticism and Indian Historiography / Gyan Prakash. 28. The Postcolonial Aura: Third World Criticism in the Age of Global Capitalism / Arif Dirlik. Le texte "Age, Race, Class, and Sex : Women Redefining Difference" de Audre Lorde a été donné en lecture au cours LIT4700.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Je suis une maudite sauvagesse = Eukuan nin matshimanitu innu-iskueu - Antane Kapesh, An (Leméac, 1976)
An Antane Kapesh signe un réquisitoire accablant contre les Blancs : « Quand le Blanc a voulu exploiter et détruire notre territoire, il n'a demandé de permission à personne, il n'a pas demandé aux Indiens s'ils étaient d'accord. »
Donné en lecture au cours POL5480, Chapitre 6 « La police et les tribunaux », p. 109-144 dans la dernière édition.
Keywords: amériques; approches et analyses; autochtones; cours; discipline; fem1000; fem3100; femmes* innues; féminisme décolonial; littérature; manifeste; militance; pol4105; pol5480; premier cycle; premières nations; québec; racisme; racisme systémique; régions géographiques; systèmes d'oppressions; thématiques; études littéraires